Effects of Sexual Abuse on Cognitive Function in College student - Rosiana, Dewi; Wangi, Eneng Nurlaili; Aslamawati, Yuli (KnE Social Sciences, 2023)
Sexual abuse is a grave societal issue, both due to its prevalence and its long-lasting consequences. In the realm of education, victims of sexual abuse often face obstacles in achieving optimal academic performance. Recently, the effects of sexual abuse on victims have garnered increased attention, particularly concerning cognitive function. In adult sexual abuse victims, deficits in short-term verbal memory have been observed, along with impaired inhibitory capacity and difficulties in verbally mediated higher cognitive abilities. Additionally, distractibility and impaired sustained attention have been identified in abused adults. This article seeks to explore the existing literature and research findings pertaining to the impact of sexual abuse on cognitive function, specifically among college students. College students undergo significant career development tasks, which necessitate robust cognitive function. The review incorporates empirical studies relevant to the effects of sexual abuse on cognitive function, while also considering the implications of these findings for future research. Keywords: sexual abuse, cognitive function, college student